2021
DOI: 10.33474/hukeno.v5i1.9223
|View full text |Cite
|
Sign up to set email alerts
|

Kewajiban Untuk Menjaga Kerahasiaan Akta Oleh Notaris Dan Karyawan Notaris Dalam Perspektif Hukum

Abstract: The purpose of this study is to find out and understand the Witnesses' Essence and Testimony in notary law. And to know and understand the legal consequences for former Notary employees who provide information to open the confidentiality of the deed. The usefulness of this research is as information material within the framework of the development of science and insights in legal disciplines, especially notary law. And as a contribution of thought in enriching the horizons for the parties concerned. According … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Notaries need to be careful in making deeds related to buying and selling, in international cooperation, international contracts, investment deeds, which are made by notaries have implications that have the potential for corruption with the mode of Money Laundering. As stipulated in 5 Muhammad Abu Hanifah, "Peran Notaris Dalam Menggali Informasi Mengenai Penerima Manfaat Berdasarkan Peraturan Presiden Nomor 13 Tahun 2018" (Tesis, Banjarmasin, Universitas Lambung Mangkurat, 2019). 6 Muhammad Rizky Hidayat, "Kedudukan dan Perlindungan Hukum Notaris Terkait Tindak Pidana Pencucian Uang" (Tesis, Banjarmasin, Universitas Lambung Mangkurat, 2020).…”
Section: Results and Discussion Deed That Must Be Reported By A Notar...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notaries need to be careful in making deeds related to buying and selling, in international cooperation, international contracts, investment deeds, which are made by notaries have implications that have the potential for corruption with the mode of Money Laundering. As stipulated in 5 Muhammad Abu Hanifah, "Peran Notaris Dalam Menggali Informasi Mengenai Penerima Manfaat Berdasarkan Peraturan Presiden Nomor 13 Tahun 2018" (Tesis, Banjarmasin, Universitas Lambung Mangkurat, 2019). 6 Muhammad Rizky Hidayat, "Kedudukan dan Perlindungan Hukum Notaris Terkait Tindak Pidana Pencucian Uang" (Tesis, Banjarmasin, Universitas Lambung Mangkurat, 2020).…”
Section: Results and Discussion Deed That Must Be Reported By A Notar...mentioning
confidence: 99%
“…Such as a scientific research article conducted by Hanifah which analyzes how the limits of notary authority to dig up information about beneficiaries based on Presidential Regulation Number 13 of 2018 and what are the legal consequences for notaries who do not explore the truth of information, regarding who are the beneficiaries of a Corporation according to Article 18 of Presidential Regulation Number 13 of 2018. 5 Another legal scientific research article is by Hidayat who analyzes how the position of Notaries in the relationship between money laundering and legal protection of Notaries in the relationship between money laundering crimes. 6 So that the formulation of the problem in this study is whether all deeds must be reported by Notaries in the prevention of Money Laundering Crimes and how the Notary's position as a whistleblower is seen from the point of view of the principle of confidentiality in his position.…”
mentioning
confidence: 99%
“…Therefore, a Notary has the right to receive an honorarium for legal services provided in accordance with their authority. 5 The notary receives an honorarium from the public for services in making authentic deeds. The honorarium received by a Notary is based on the economic and sociological value of each deed he makes, regulated in Article 36 and Article 37 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Office of a Notary.…”
mentioning
confidence: 99%
“…Kanter, Etika Profesi Hukum: Sebuah Pendekatan Religius (Jakarta: Storia Grafika, 2001) 4. Sjaifurrachman dan Habib Adjie, Aspek Pertanggungjawaban Notaris dalam Pembuatan Akta (Bandung: Mandar Maju, 2011) 5. Salim HS., Teknik Pembuatan Akta Satu (Konsep Teoritis, Kewenangan Notaris, Bentuk dan Minuta Akta) (Jakarta: PT.…”
unclassified